(untitled) (Vallis Aurea, 2016)
The aim of this paper is to present the composition and functioning of the EU institutions involved in receiving, analysing, approval or rejection of the application for the use of genetically modified organisms. The manner of participation of each institution is presented by using the comparative and historical method, as well as the method of analysis. The advantage of these methods is a detailed analysis of the rights and responsibilities of all participants in the approval process for genetically modified organisms. The paper analyses all the EU institutions that are directly or indirectly associated with the approval procedure, and those are: European Food Safety Authority, European Parliament, European Commission and Court of Justice of the European Union. The problem of the whole institutional framework is an insufficient contribution of the constituent activity of the EU member states and their national authorities and whole process should be based more on the principle of subsidiarity.